Answer:
6 and -1
Explanation:
If you take the equation and set it to be 0, you can find the input values that make it 0.
![x^2-5x-6=0](https://img.qammunity.org/2023/formulas/mathematics/college/r6az9q30edgvexcn1ghsj2vv7k8wp72x74.png)
Since this is a quadratic, equation you can use the quadratic formula with the values:
The quadratic formula is:
![x=(-b \pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/868u5m90l9qkg6ux29llh7cxzyq1z69cya.png)
If you plug the values for a, b, and c, you get:
x = 6 and x = -1